Identification of Gastrointestinal Worms Egg on Spotted Deer (Axis axis) and Bawean Deer (Axis kuhlii) at Wonorejo Bibit Park and Surabaya Flora Park - Achmad Hasan Sahani; Sri Mulyati; Tri Bhawono Dadi; Sri Mumpuni Sosiawati; Kusnoto Kusnoto; Ratna Damayanti (Journal of Parasite Science (JoPS), 2018)
The purpose of this study was to identify the type of gastrointestinal worms egg of Spotted Deer (Axis axis) and Bawean Deer (Axis kuhlii) at Wonorejo Bibit Park and Surabaya Floral Park. The research was conducted in October-December 2017 used total 50 specimen of sample faeces, 40 sample faeces from Surabaya Flora Park and 10 sample faeces from Wonorejo Bibit Park, the samples analyzed at the Department of Parasitology Veterinary, Faculty of Veterinary Medicine, Airlangga University. The results showed that the degree of helmint gastrointestinal in Bawean Deer and Spoted Deer at Wonorejo Bibit Park showed 0% while at the Surabaya Flora Park is 15%. The type of worm found were Trematoda class it was Fasciola sp. The resuls of the analysis used Chi-Square test and showed no significantly differences degree of gastrointestinal helminth infection (p>0.05) .